Oxygen uptake efficiency slope: a reliable surrogate parameter for exercise capacity in healthy and cardiac children?. Issue 12 (30th July 2020) - Gavotto, Arthur; Vandenberghe, D'arcy; Abassi, Hamouda; Huguet, Helena; Macioce, Valerie; Picot, Marie-Christine; Guillaumont, Sophie; Matecki, Stefan; Amedro, Pascal
Abstract : Objectives: Cardiopulmonary exercise test (CPET) provides accurate evaluation of physical capacity and disease severity in children with congenital heart disease (CHD). However, full participation to obtain optimal measure of VO2max may be difficult. As an alternative, the oxygen uptake efficiency slope (OUES) is a reproducible and reliable parameter measured during CPET, which does not require a maximal exercise to be interpretable. This study aimed to evaluate the OUES of a large cohort of children with CHD, in comparison with healthy controls. We also intended to identify, in this specific population, the clinical and CPET variables associated with the OUES. Methods: This cross-sectional study was carried out between November 2010 and September 2015 in two tertiary care paediatric and congenital cardiology centres. Results: 709 children were included (407 CHD and 302 healthy controls). The association of clinical characteristics with weight-normalised OUES (OUESkg ) was studied using a multivariable analysis. The mean OUESkg was significantly lower in CHD than in healthy controls (38.6±8.5 and 43.9±8.5; p<0.001, respectively), especially in the most severe CHD. The OUESkg correlated with VO2max (r=0.85, p<0.001), with cut-off values for normal exercise capacity of 38.4 in boys and 31.0 in girls. The decrease of OUESkg was associated with increased age, increased Body Mass Index, number of cardiac catheter or surgical procedures, female gender and decreased forced vital capacity (Z-score). Conclusion: The OUES is significantly impaired in children with CHD and strongly correlates with VO2max . The OUES has the same clinical determinants as VO2max and therefore may be of interest in submaximal exercise. Trial registration number: NCT01202916 .